Benefits of smart yachting technologies for Russian yachting reserve training service - Ryabchikov, V. V.; Ashkinazi, S. M.; Kulikov, V. S.; Skok, N. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze benefits of the modern smart yachting technologies for the national yachting sport reserve technical and tactical skills training service.